A Comparison of Face-Down Positioning and Adjustable Positioning After Pars Plana Vitrectomy for Macular Hole Retinal Detachment in High Myopia - Gao, Yan; Ruan, Ting; Chen, Nan; Yu, Bin; Xing, Xiaoli; Du, Qing; Qi, Yan; Li, Jun (Frontiers in Medicine, 2022)
Purpose: To compare the anatomical and functional outcomes of macular hole retinal detachment(MHRD) in high myopia after pars plans vitrectomy(PPV) with face-down positioning and adjustable positioning. Methods: Fifty-three eyes from 53 patients with MHRD were included in this study. All patients received PPV with silicon oil for tamponade and then subdivided into 2 groups: 28 were included in a face-down positioning group and 25 were included in the adjustable positioning group. Patients were followed up for at last 6 months. The main outcome was the rate of anatomical MH closure and retinal reattachment. Secondary outcome measures were best-corrected visual acuity and postoperative complications. Results:There was no significant difference in the rate of MH closure (53.6% VS 72.0%, P=0.167) and retinal reattachment (100% VS 96%, P=0.472) between the face-down group and adjustable group. Compared with the mean preoperative BCVA, the mean postoperative BCVA at the 6-month follow-up improved significantly in both two groups (P=0.000, both). But there was no significant difference in the mean postoperative BCVA (P=0.102) and mean BCVA improvement (P=0.554) at 6-month after surgery between the two groups. There was no significant difference in the high IOP after surgery between the two groups (53.6% VS 44.0%, P=0.487). There were no other complications occurred during the follow-up. Conclusion: Adjustable positioning after PPV with silicon oil tamponade for MHRD repair is effective and safe. Face-down positioning seems not to be necessary for all patients with MHRD.